Analysis of Outsourcing System and Work Motivation on Employee Performance - Neng Eti Setiawati (Journal of Business and Behavioural Entrepreneurship, 2021)
Background - Currently, many companies are implementing outsourcing systems for their company's HR management. Outsourcing is a company that uses human resources from other parties (external) to carry out work activities that are usually handled by internal staff and resources. The problem that exists is because the outsourcing system affects the performance of employees at a food ingredients factory in Cilegon, where there are still high complaints from clients regarding the decline in the performance of forklift operator employees placed in their company. This shows the inaccuracy at work leads to a lack of employee motivation. Employee motivation problems can be the cause of low employee performance in a company.